2018
DOI: 10.3928/23258160-20180814-04
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Brimonidine on Retinal Pigment Epithelial Cells and Müller Cells Exposed to Amyloid-Beta 1–42 Peptide In Vitro

Abstract: BACKGROUND AND OBJECTIVE: To evaluate whether brimonidine can prevent cytotoxicity in human retinal pigment epithelial (RPE) and Müller (MIO) cells after exposure to amyloid-beta 1–42 (Aβ42). MATERIALS AND METHODS: An in vitro model of geographic atrophy (GA), which is an end-stage complication of age-related macular degeneration (AMD), simulated with the application of Aβ42 in cell culture. RPE and MIO cells were pretreated with brimonidine for 6 hours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…32 Several medical agents, such as Brimonidine, Puerarin and Baicalin, have been shown to alleviate intracellular pyroptosis and viability damage through preventing Aβ-induced oxidative stress damage and inflammatory activity. [33][34][35] Also, sirtuin 1 (SIRT1) has been identified as a protective factor, which suppresses the activation of NF-κB signalling pathway induced by Aβ in AMD. 36 These results have shown the proinflammatory role of Aβ in AMD.…”
Section: Aβ Induces Inflammasome In Amdmentioning
confidence: 99%
“…32 Several medical agents, such as Brimonidine, Puerarin and Baicalin, have been shown to alleviate intracellular pyroptosis and viability damage through preventing Aβ-induced oxidative stress damage and inflammatory activity. [33][34][35] Also, sirtuin 1 (SIRT1) has been identified as a protective factor, which suppresses the activation of NF-κB signalling pathway induced by Aβ in AMD. 36 These results have shown the proinflammatory role of Aβ in AMD.…”
Section: Aβ Induces Inflammasome In Amdmentioning
confidence: 99%
“…Upon comparison of the cell viability of the self-assembled films with and without Brim with untreated cells, it is clear that extracts of the films do not show any cytotoxicity. In fact, it is clear that there is a metabolic stimulation of the cells, which can be attributed to the presence of Brim , which has been described to have a protective role in preventing oxidative stress of retinal pigment epithelial (RPE) and Müller cells, , thus contributing to its increased viability. It has also been shown that polymers from the family of poly­(β-amino esters) can promote cell viability, as shown in HEK293 cells …”
Section: Resultsmentioning
confidence: 99%
“…Based on these studies, accumulation of Aβ1-42 in retinal cells can result in activation of PARP1 and subsequent repression of sirtuin 1 (SIRT1), ultimately leading to increased expression of caspase-3 and caspase-9, hence accelerated apoptosis [67]. The deleterious effects of amyloid aggregates are not restricted to epithelial pigment cells, as these complexes can also negatively affect Muller cells or retinal gliocytes, which are involved in neuroprotection and immunity [68].…”
Section: Cellular and Molecular Markers Of Retinal Hemorrhagementioning
confidence: 99%